2015
DOI: 10.1177/0146167215595606
|View full text |Cite
|
Sign up to set email alerts
|

Immorality East and West

Abstract: What makes some act immoral? While Western theories of morality often define harmful behaviors as centrally immoral, whether or not this is applicable to other cultures is still under debate. In particular, Confucianism emphasizes civilized behavior as fundamental to moral excellence. We designed three studies examining how the word "immoral" is used by Chinese and Westerners. Layperson-generated examples were used to examine cultural differences in which behaviors are called "immoral" (Study 1, N = 609; Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 61 publications
4
55
0
1
Order By: Relevance
“…Participants were recruited via wjx.cn, a reliable Chinese data collection platform similar to Qualtrics Online Sample and widely used in prior studies [38,39]. The sample size of this platform is 2.6 million, which enabled us to cover a relatively diverse sample across industries and other related job characteristics.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Participants were recruited via wjx.cn, a reliable Chinese data collection platform similar to Qualtrics Online Sample and widely used in prior studies [38,39]. The sample size of this platform is 2.6 million, which enabled us to cover a relatively diverse sample across industries and other related job characteristics.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Groups may have more flexibility in establishing norms for how ingroup members conduct themselves compared to how people treat each other. Consistent with this, culturally-specific conceptions of the self lead to robust variation in the moral status of purity norms compared to relatively stable endorsement of harm norms [52,53]. Even groups within the United States (i.e., liberals and conservatives) differ in their endorsement of purity but not harm norms [7,44].…”
Section: Discussionmentioning
confidence: 93%
“…Harm norms are more universally held than purity norms [39,53], and people may be prone to seeing any negative dyadic interaction through the lens of a perpetrator harming a victim [45]. Future studies should investigate whether harm does indeed have a more specific link with the impact an action has on others (versus oneself) in populations that are less harm-focused, such as non-Western societies [52,53,61]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study of Chinese lay prototypes of immoral behaviors, we found a puzzling disconnect between what was acknowledged to be most harmful (e.g., killing people) and what was called immoral; the Chinese word for immoral was most applicable to behaviors that were particularly uncultured or uncivilized, such as spitting in the street or disrespecting parents, and less applicable to criminally harmful behaviors such as stealing or killing (Buchtel et al 2015). This suggests that the categories of antisocial behaviors are differently organized in Confucian heritage cultures than they are in Western heritage cultures, where instead behaviors have been divided into those that are impermissible (very harmful) versus not (Buchtel et al 2015). Historically, morality in China has been based on the teaching of Confucian virtues such as benevolence and propriety, while criminalspresumably beyond the motivational reach of virtuewere dealt with through the criminal law system (Bakken 2000).…”
Section: Introductionmentioning
confidence: 82%